Relationship between seasons and postpartum depression: A systematic review and meta‐analysis of cohort studies. Issue 6 (3rd May 2022) - Tung, Tao‐Hsin; Jiesisibieke, Dina; Xu, Qinyi; Chuang, Yen‐Ching; Jiesisibieke, Zhu Liduzi
Abstract: Objective: As the reproduction season's effect on the mental health status is unknown, this study aims to explore the association between seasons and postpartum depression. Methods: A comprehensive search in databases, including PubMed, Cochrane Library, and EMBASE, was performed to identify studies reporting the relationship between reproduction season and postpartum depression. The latter was assessed using certain methods. Moreover, the study design and duration, sample size, the definition of four seasons, outcome assessment, method, and conclusion were extracted. Two independent authors screened the studies independently, and PRISMA 2020 was used as the reporting standard (PRISMA registration ID is 284524). Results: A total of five studies including 103, 986 participants met our criteria. In the sensitivity analysis, the result of the meta‐analysis shows that women who gave birth in spring, summer, or autumn had a lower risk of postpartum depression compared to those who gave birth in winter (RR: 0.83; 95% confidence interval [CI]: 0.78–0.88). Conclusion: Women who gave birth in the other seasons were less likely to have postpartum depression compared to those who gave birth in winter. This result could help couples make overall decisions and help the puerpera take preventive measures against postpartum depression. Abstract : Women who gave birth in the other seasons were less likely to have postpartum depression compared to those who gave birth in winter. This result could help couples make overall decisions and help the puerpera take preventive measures against postpartum depression.